2010
DOI: 10.1007/s12020-010-9334-4
|View full text |Cite
|
Sign up to set email alerts
|

Chitotriosidase activity predicts endothelial dysfunction in type-2 diabetes mellitus

Abstract: The enzyme chitotriosidase (ChT) is secreted by activated macrophages and play active role in human immune response. ChT activity is increased in atherosclerosis in association to the extent of the disease. We investigated the relevance of ChT to endothelial functions and insulin resistance in patients with T2DM. Forty newly diagnosed and untreated patients with T2DM (male 17; age 47.0 ± 6.2 years) and 50 healthy volunteers (male 21; age 50.2 ± 8.8 years) were enrolled. Plasma asymmetric dimethyl arginine (ADM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 40 publications
1
25
1
Order By: Relevance
“…In this light, the relationship we observed of all examined GH18 proteins with LE may indicate their connection with progression of late vascular complications [16]. The results imply that increased CHIT1 activity may be a predictor of endothelial dysfunction [15]. …”
Section: Chit1 and Dmmentioning
confidence: 96%
See 1 more Smart Citation
“…In this light, the relationship we observed of all examined GH18 proteins with LE may indicate their connection with progression of late vascular complications [16]. The results imply that increased CHIT1 activity may be a predictor of endothelial dysfunction [15]. …”
Section: Chit1 and Dmmentioning
confidence: 96%
“…Nowadays, there is little evidence showing that serum CHIT1 activity is increased in patients with newly diagnosed, untreated, and uncomplicated type 2 DM (T2DM) [15,16]. A recent study reported involvement of neutrophils in the pathogenesis of insulin resistance.…”
Section: Chit1 and Dmmentioning
confidence: 99%
“…Serum CHIT1 activity is increased in patients with newly diagnosed, untreated, and uncomplicated type 2 DM. This elevation is positively associated with the age, plasma glucose, and asymmetric dimethylarginine (ADMA) levels of those patients [76]. ADMA is naturally occurring component of human blood plasma as an analogue of Larginine, and is formed as a metabolic byproduct of protein turnover in any cell types of the human body [75].…”
Section: Biological Roles Of Chit1 In Pathogenic Conditionsmentioning
confidence: 99%
“…Elevated levels of ADMA inhibit nitric oxide synthesis and impair endothelial function; these levels are increased in patients with DM [75]. The correlation between elevated CHIT1 and ADMA levels could be a sharp biomarker of predicting endothelial dysfunction, which contributes to progression of atherosclerotic lesions, in type 2 DM patients [76]. …”
Section: Biological Roles Of Chit1 In Pathogenic Conditionsmentioning
confidence: 99%
“…Malaguernera et al showed that Chitotriosidase activity and the levels of CHIT mRNA increased by stimulation of macrophages with IFN-γ, TNF-α, and LPS [19]. Although an increase in chitotriosidase activity, as well as inflammatory molecules in patients with DM, has been shown], so far there is no data on the effect of PPAR-γ activation on chitotriosidase activity in patients with insulin resistance [20]. Rosiglitazone treatment increased chitotriosidase activity which is released from activated macrophages probably due to PPAR-γ activation-induced expression of scavenger receptors (CD36) and increased uptake of oxLDL in macrophages [11].…”
Section: Discussionmentioning
confidence: 99%